THE RELATIONSHIP OF KNOWLEDGE OF WOMEN OF FERTILIZING AGE (WUS) AND THE USE OF IUD CONTRACEPTION IN THE SIBANGGOR PUSKESMAS KEC. PUNCAK SORIK MARAPI MANDAILING NATAL REGENCY YEAR 2023 - Fausiah; Khairunnisa Situmorang; Rosmani Sinaga; Alfrina Rumapea; Humaida Hanim; Ariska Fauzianty (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Contraception is an attempt to regulate pregnancy and prevent pregnancy. (Prawirohardjo, 2010). Of the many contraceptive methods, one of the rational, effective and efficient contraceptives is the IUD which plays a role in the success of National Family Planning (BKKBN, 2009). The choice of contraception is largely determined by the acceptor’s knowledge of the contraceptive. Apart from that, factors that influence the use of contraception include reviewing the physical condition, economic, social situation, level of education and history of the family planning acceptor’s parity. Meanwhile, around 12 million PUS have not used contraception due to limited access, as well as lack of knowledge, fear of side effects and social, cultural and religious problems (BKKBN, 2009). This research uses a descriptive correlation research design with a cross sectional approach which is a study of the relationship between two variables in a situation or group of subjects which was carried out to see the relationship between one variable and another, which aims to determine the relationship between knowledge of women of childbearing age (WUS) and the use of IUD contraception at the Puskesmas in Sibanggor District Health Center. Puncak Sorik Marapi Kab. Mandailing Christmas in 2023. The results of statistical analysis using the chi square test stated that there was a relationship between knowledge of women of childbearing age (WUS) and the use of IUD contraception at the Sibanggor District Health Center. Puncak Sorik Merapi Regency. Mandailing Christmas 2023 with a p-value of 0.006 (p-value 0.05). Frequency distribution of knowledge of Women of Childbearing Age (WUS) about IUD from 45 respondents. It was found that the majority of respondents had less knowledge, 21 people (65.6%), and a minority of respondents 11 people (34.4%) had good knowledge.